The use of Bovine Somatotropin (BST) in dairy cattle - J. Estrada; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1989)
We all have heard about the use of BST in lactating dairy cattle during the last 6 to 8 years, but what is BST? Bovine somatotropin is another dairy management tool developed to improve the efficiency and reduce the cost of producing milk. It is the newest in a list of technological advances in the dairy industry, such as genetic improvements, nutrition, health, housing, milking equipment and techniques, embryo transfer, and DHI records. BST is a natural protein produced in the anterior pituitary gland of all cattle. Like other proteins, BST is composed of various amino acids (190-199). BST is bovine growth hormone, somatotropin. It helps to allocate energy from feed to meet the physical needs of the cows, such as growth in young animals, milk production in mature animals, and other functions in the body.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Bovine Somatotropin (BST); Milk production